Regenerating cellulose from ionic liquids for an accelerated enzymatic hydrolysis - Zhao, Hua; Jones, Cecil L.; Baker, Gary A.; Xia, Shuqian; Olubajo, Olarongbe; Person, Vernecia N. (Journal of biotechnology, 2009)
The efficient conversion of lignocellulosic materials into fuel ethanol has become a research priority in producing affordable and renewable energy. The pretreatment of lignocelluloses is known to be key to the fast enzymatic hydrolysis of cellulose. Recently, certain ionic liquids (ILs) were found capable of dissolving more than 10 wt% cellulose. Preliminary investigations [Dadi, A.P., Varanasi, S., Schall, C.A., 2006. Enhancement of cellulose saccharification kinetics using an ionic liquid pretreatment step. Biotechnol. Bioeng. 95, 904–910; Liu, L., Chen, H., 2006. Enzymatic hydrolysis of cellulose materials treated with ionic liquid [BMIM]Cl. Chin. Sci. Bull. 51, 2432–2436; Dadi, A.P., Schall, C.A., Varanasi, S., 2007. Mitigation of cellulose recalcitrance to enzymatic hydrolysis by ionic liquid pretreatment. Appl. Biochem. Biotechnol. 137–140, 407–421] suggest that celluloses regenerated from IL solutions are subject to faster saccharification than untreated substrates. These encouraging results offer the possibility of using ILs as alternative and non-volatile solvents for cellulose pretreatment. However, these studies are limited to two chloride-based ILs: (a) 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), which is a corrosive, toxic and extremely hygroscopic solid (m.p. ∼ 70 °C), and (b) 1-allyl-3-methylimidazolium chloride ([AMIM]Cl), which is viscous and has a reactive side-chain. Therefore, more in-depth research involving other ILs is much needed to explore this promising pretreatment route. For this reason, we studied a number of chloride- and acetate-based ILs for cellulose regeneration, including several ILs newly developed in our laboratory. This will enable us to select inexpensive, efficient and environmentally benign solvents for processing cellulosic biomass. Our data confirm that all regenerated celluloses are less crystalline (58–75% lower) and more accessible to cellulase (>2 times) than untreated substrates. As a result, regenerated Avicel ® cellulose, filter paper and cotton were hydrolyzed 2–10 times faster than the respective untreated celluloses. A complete hydrolysis of Avicel ® cellulose could be achieved in 6 h given the Trichoderma reesei cellulase/substrate ratio (w/w) of 3:20 at 50 °C. In addition, we observed that cellulase is more thermally stable (up to 60 °C) in the presence of regenerated cellulose. Furthermore, our systematic studies suggest that the presence of various ILs during the hydrolysis induced different degrees of cellulase inactivation. Therefore, a thorough removal of IL residues after cellulose regeneration is highly recommended, and a systematic investigation on this subject is much needed.